Zeroing in on AIDS and global health Post-2015 - Buse Kent; Blackshaw Ruth; Ndayisaba Marie-Goretti (BMC, 2012)
Abstract December 1st marks World AIDS Day with the theme 'Getting to zero'. Three years ago, UNAIDS articulated what was then considered to be an ambitious vision, the aspiration for zero new HIV infections and zero-AIDS related deaths underpinned by zero discrimination. As we imagine the Post-2015 development agenda, we can and should reconceptualise this vision as a set of concrete goals. This Viewpoint argues that today's rapidly changing world, including its shifting geo-political and economic landscape, requires policy responses that are context-sensitive. We highlight the Shared Responsibility-Global Solidarity agenda, as pioneered by the African Union in its recent Roadmap on AIDS, tuberculosis, and malaria, to illustrate ways in which global health can be re-thought to tackle twenty-first century challenges. In light of the emerging debate on what a Post-2015 development agenda and accountability framework should look like, we argue that the AIDS response offers lessons as a pathfinder which can pave the way for global health responses in which the most marginalised are at the centre of the debate, human rights are protected under the rule of law, strong accountability is in place for results for people, and community and participatory processes are the norm. These hard-learned and -won principles of the AIDS response are critical if we are to realize a world in which there is zero inequality and health justice for all.